Neuromarketing e a relação com o marketing sensorial no estudo do comportamento dos consumidores nas vendas online - Rocha, Ana Isabel Mendonça (2021)
The digital age has grown steeply over the past few years and has been gaining more and more consumers and changing their behavior. Neurosciences combined with marketing, constitute a new paradigm with great potential, with regard to the deep knowledge of the consumer and his buying behavior: Neuromarketing. Neuromarketing has a strong scientific component that studies and physiologically defines the mechanisms underlying cognition, with a specific focus on the neural bases of mental processes and their behavioral manifestations and an economic and social component in which Marketeers question themselves about traditional methods to learn deeply your customer and apply one-to-one marketing to its full potential, create loyalty relationships and avoid the lack of differentiation that still occurs in some companies. The main objective of this work was to understand the relationship that exists between sensory marketing, that is, the five senses and consumer behavior, because the knowledge of this dynamic is very important for the definition of companies' digital marketing strategies. The exploratory study, using an online questionnaire that aimed to understand the existence of a relationship between sensory marketing and consumer behavior in relation to different websites. The results concluded that there are, in fact, responses to sensory stimuli on an e-commerce website, and it was possible to prove that all stimuli positively influence consumer satisfaction during the online experience.